You are here : from the compass to GPS, the history and future of how we find ourselves - Bray, Hiawatha (Basic Books, 2014)
"The story of the rise of modern navigation technology, from radio location to GPS-and the consequent decline of privacy What does it mean to never get lost? You Are Here examines the rise of our technologically aided era of navigational omniscience-or how we came to know exactly where we are at all times. In a sweeping history of the development of location technology in the past century, Bray shows how radio signals created to carry telegraph messages were transformed into invisible beacons to guide ships and how a set of rapidly-spinning wheels steered submarines beneath the polar ice cap. But while most of these technologies were developed for and by the military, they are now ubiquitous in our everyday lives. Our phones are now smart enough to pinpoint our presence to within a few feet-and nosy enough to share that information with governments and corporations. Filled with tales of scientists and astronauts, inventors and entrepreneurs, You Are Here tells the story of how humankind ingeniously solved one of its oldest and toughest problems-only to herald a new era in which it's impossible to hide."--Resumé vydavatele
Keywords: navigace -- dějiny; navigační technika -- dějiny; radionavigace -- dějiny; geografické informační systémy -- dějiny; geografická data; geografická poloha; navigation -- history; navigation technology -- history; radio navigation -- history; geographical information systems -- history; geographical data; geographical position; populárně-naučné publikace; popular works